Trial of Foreign Nationals: Distinction Between Consular and Diplomatic Assistance Toward Capital Punishment (Case Study of Australian Nationals Facing Capital Punishment in Indonesia) - Sitamala, Affandi (Fakultas Hukum Universitas Negeri Semarang, 2020)
The movement of foreign nationals has recently entered a new level of relationship between government. A great number of foreign nationalÃ¢â‚¬â„¢s travel or live abroad than before is the main issues. The protection of nationals when they are abroad is accepted as an important function of government. States recognize each otherÃ¢â‚¬â„¢s right to exercise protection over their own nationals. Protection is affected through a consular official assigned assign by the state origin. The state that appoints a consul is called the sending state while the state in which the consul works is called the Ã¢â‚¬Å“receivingÃ¢â‚¬Â state. Sending state consul visit sending-state nationals in receiving-state jails. However, the question remains on how the government and the foreign nationals fulfilling the right and obligation to one another. One of the common situations is when foreign nationals being detained abroad. Furthermore, how consular and diplomatic functioned toward capital punishment that Herein lays the paradox, I would like to argue on how one country should fulfill its obligations under the international law (Vienna Convention on Diplomatic Relations and Vienna Convention on Consular Relations). Hence, the case illustrates how receiving and sending state fulfilling their responsibilities.